Susceptibility of SARS-CoV-2 to UV irradiation - Heilingloh, Christiane Silke; Aufderhorst, Ulrich Wilhelm; Schipper, Leonie; Dittmer, Ulf; Witzke, Oliver; Yang, Dongliang; Zheng, Xin; Sutter, Kathrin; Trilling, Mirko; Alt, Mira; Steinmann, Eike; Krawczyk, Adalbert (American journal of infection control, 2020)
•SARS-CoV-2 is highly susceptible to irradiation with ultraviolet light.•High viral loads of 5 * 106 TCID50/ml SARS-CoV-2 can be inactivated in 9 minutes by UVC irradiation.•UVC irradiation represents a suitable disinfection method for SARS-CoV-2. The coronavirus SARS-CoV-2 pandemic became a global health burden. We determined the susceptibility of SARS-CoV-2 to irradiation with ultraviolet light. The virus was highly susceptible to ultraviolet light. A viral stock with a high infectious titer of 5 × 106 TCID50/mL was completely inactivated by UVC irradiation after nine minutes of exposure. The UVC dose required for complete inactivation was 1,048 mJ/cm2. UVA exposure demonstrated only a weak effect on virus inactivation over 15 minutes. Hence, inactivation of SARS-CoV-2 by UVC irradiation constitutes a reliable method for disinfection purposes in health care facilities and for preparing SARS-CoV-2 material for research purpose.